2019
DOI: 10.1177/1559325819888317
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene Oxide: Cancer Evidence Integration and Dose–Response Implications

Abstract: The International Agency for Research on Cancer (IARC) and the United States Environmental Protection Agency (USEPA) classified ethylene oxide (EtO) as a known human carcinogen. Critically, both noted that the epidemiological evidence based on lymphoid and breast cancers was “limited,” but that the evidence in animal studies was “sufficient” and “extensive” (respectively) and that EtO is genotoxic. The USEPA derived one of the highest published inhalation unit risk (IUR) values (3 × 10−3 per [µg/m3 EtO]), base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 51 publications
0
19
0
2
Order By: Relevance
“…The evaluations of both IARC and US-EPA are being questioned. Thus, Vincent et al (Vincent et al 2019 ) argued that higher quality epidemiological studies demonstrated no increased risk of breast cancers or lymphohaematopoietic malignancies, and that toxicological studies and studies of early effect biomarkers in animals and humans provided no strong indication that EO causes lymphohaematopoietic or mammary cancers. In consequence, animal data were addressed as being inadequate to define the actual dose–response shape or predict tumour response at very low doses with any confidence.…”
Section: Process-related Contaminantsmentioning
confidence: 99%
“…The evaluations of both IARC and US-EPA are being questioned. Thus, Vincent et al (Vincent et al 2019 ) argued that higher quality epidemiological studies demonstrated no increased risk of breast cancers or lymphohaematopoietic malignancies, and that toxicological studies and studies of early effect biomarkers in animals and humans provided no strong indication that EO causes lymphohaematopoietic or mammary cancers. In consequence, animal data were addressed as being inadequate to define the actual dose–response shape or predict tumour response at very low doses with any confidence.…”
Section: Process-related Contaminantsmentioning
confidence: 99%
“…For example, single-use supplies are often sterilized using ethylene oxide (ETO), a known carcinogen. 28 As a localized example of the adverse public health effects of medical care, Sterigenics, a medical supply sterilization facility north of Chicago, was forced to close in 2019 due to public outcry of the use of ETO gas. A recent report by the Environmental Protection Agency showed increased cancer rates in that community, validating these concerns.…”
Section: Taking Action To Transition To Climate-smart Radiation Oncol...mentioning
confidence: 99%
“…After an extensive review of the available data, the US Environmental Protection Agency (EPA) Integrated Risk Information System (IRIA) program concluded (Office of Research and Development US EPA, 2016) that the "…confidence in the hazard characterization of EtO as 'carcinogenic to humans' is high." Using this data, the EPA has assigned a total cancer unit risk (inhalation unit risk) estimate for EtO of 3.3 × 10 -3 μg/m 3 (~12 ppt), though recent studies (Vincent et al, 2019;Texas Commission on Environmental Quality, 2020) suggests that this unit risk estimate may be too low and a value of ~2 ppb may be more appropriate.…”
Section: Introductionmentioning
confidence: 99%